Higher Water‐Splitting Performance of Boron‐Based Porous CoMnB Electrocatalyst over the Benchmarks at High Current in 1 m KOH and Real Sea Water. (30th July 2022) - Lin, Shusen; Habib, Md Ahasan; Mandavkar, Rutuja; Kulkarni, Rakesh; Burse, Shalmali; Chung, Young‐Uk; Liu, Changsheng; Wang, Zilin; Lin, Shiwei; Jeong, Jae‐Hun; Lee, Jihoon
Abstract: The development of highly efficient and stable electrocatalysts at an affordable cost is an essential component for the large‐scale implementation of green hydrogen production. In this work, the fabrication of porous CoMnB electrocatalyst is demonstrated with the incorporation of boron into the Co‐Mn matrix by an electrochemical approach for bifunctional water electrocatalysis for the first time. The optimized CoMnB electrocatalyst demonstrates an excellent bifunctionality with a low 2‐E turnover voltage of 1.59 V at 20 mA cm −2 in 1 m KOH. The CoMnB shows a comparable water‐splitting current at low current range as compared with the standard benchmark electrodes of Pt/C||RuO2 in 1 m KOH. Then, the CoMnB outperforms the benchmarks at above 800 mA cm −2, indicating a better H2 and O2 generation performance at the industrial operational condition of high current range. The CoMnB also exhibits superior electrocatalytic activity in real sea water +1 m KOH. In addition, the porous CoMnB electrocatalyst exhibits an excellent stability with stable current for continuous 72 h operation at high current and excellent repeatability after 1000 cycles. The result ranks the CoMnB as one of the best transition metal‐based water‐splitting electrocatalysts at low cost with an easy fabrication approach. Abstract : A boron‐incorporating porous CoMnB electrocatalyst demonstrates a better water‐splitting performance over the benchmark electrodes of Pt/C and RuO2 at above 800 mA cm −2 with a cell voltage of 2.33 V in 1 m KOH.